Dislodged Bonded Molar Tube into Wound during Orthognathic Surgery - Tengku Aszraf Tengku Shaeran; A. R. Samsudin (Hindawi Limited, 2018)
Introduction. Dislodgement of orthodontic appliance into operation wounds may occur while performing orthognathic surgery. Its occurrence is commonly associated with bonded upper molar tube. Case Report. A 25-year-old gentleman presented with recurrent upper right vestibular abscess three months following a bimaxillary orthognathic surgery. A bonded molar orthodontic tube had dislodged into the wound during the operation. The clinical presentation initially mimics an odontogenic infection until our investigations revealed that it originated from the dislodged appliance. The abscess was drained, the wound site was explored, and the molar tube and neighbouring rigid fixation plates and screws were removed. The patient recovered well following the procedure. Conclusion. Dislodged metal orthodontic appliance in oral wound acts as a foreign body that may exert allergic reactions, infection, or inflammation. Pre- and postoperative intraoral examination of fixed orthodontic appliances including its count should be recorded in orthognathic surgery protocol.